An examination of mercury levels in the coastal environment and fish of Cote d'Ivoire. (August 2022) - Mason, R.P.; Coulibaly, M.; Hansen, G.; Inman, H.; Myer, P.K.; Yao, K.M.
Abstract: Artisanal and small-scale gold mining (ASGM), energy production and other industrial inputs are a major source of anthropogenic mercury (Hg) to the aquatic environment globally, and these inputs have led to environmental contamination and human exposure. While studies have documented the effects of Hg inputs to rivers and marine waters of the West African region, estuarine waters of Cote d'Ivoire have been understudied, besides the waters surrounding Abidjan. To fill this gap, and to examine the potential for human exposure to methylmercury (MeHg), we measured the concentrations of total Hg, MeHg, and ancillary parameters in water (dissolved and particulate phases), sediment and fish to determine the extent of environmental impact and the potential for MeHg exposure for people consuming these fish. Levels of Hg and MeHg in sediment were elevated in the vicinity of the urban environment (up to 0.3 ng/g dry weight (dw) MeHg and 623 ng/g dw total Hg) and lowest in the more remote estuarine environments. Measurements of Hg in tuna and other larger pelagic coastal species indicated that levels were elevated but comparable to other North Atlantic regions. However, levels of Hg in fish, even smaller estuarine species, were such that the rural and urban populations are potentially being exposed to unsafe levels of MeHg, primarily as a result of the relatively high fish consumption in Cote d'Ivoire compared to other countries. Overall, both local point sources and the transport of Hg used in interior ASGM activities are the sources for Hg contamination to these coastal waters. Graphical abstract: Image 1 Highlights: Mercury levels in water and sediment were elevated near urban areas. Fish mercury levels were sufficiently elevated to pose risk to frequent consumers. Methylmercury levels in water did not correlate with those of sediment. Sediment total mercury, but not methylmercury, correlated with organic content. Mercury in tuna species were comparable to other studies in the North Atlantic.